Community knowledge of Amorphophallus muelleri Blume: Cultivation and utilization in Central Java, Indonesia - Baiq Farhatul Wahidah; Norma Afiati; Jumari Jumari (Society for Indonesian Biodiversity, 2021)
Abstract. Wahidah BF, Afiati N, Jumari. 2021. Community knowledge of Amorphophallus muelleri Blume: Cultivation and utilization in Central Java, Indonesia. Biodiversitas 22: 2731-2737. Porang (Amorphophallus muelleri Blume) is a member of the Araceae edible family currently popular on Java island, Indonesia. In the last five years, this plant which has high economic value due to its various benefits as a food plant and medicinal plant has been cultivated in Central Java. This study aims to determine the knowledge of the people in Central Java about porang plant, its cultivation, and its use in people's lives. The method used is a qualitative method by applying data collection techniques through interviews, observation and documentation. Besides general interviews, this study gains more information from some informants whose purposively chosen amongst the respondents as people knowledgeable about porang in general, and in particular A. muelleri. Results showed that people in Central Java do have knowledge about porang plant even though it was not used as food ingredient. Public knowledge about porang cultivation is obtained from various sources including social media and people who strive for porang with success. Therefore, since the community is currently aware of the potential and economic values of porang, they have started to cultivate it. Porang has enormous potential to be developed in the future and provide welfare for the community.